The Effectiveness of Oxytoxin Massage Towards Increasing Breast Milk Production in Aek Haruaya Village, Portibi District - Wulandari, Ratna; Ramadhani Nainggolan; Riska Yanti Harahap; Ica Fauziah Harahap (International Journal of Public Health Excellence (IJPHE), 2022)
Mother's milk is the best food for conceiving a baby because it is a perfect natural food, easily digested by babies and has nutrients that are in accordance with the baby's needs for growth, immunity and preventing various diseases as well as for baby's intelligence, safe and guaranteed cleanliness because it is directly given to babies to avoid digestive disorders such as diarrhea, vomiting and so on. Exclusive breastfeeding in Indonesia has not reached the target of exclusive breastfeeding that has been set at 80%. The cause of low exclusive breastfeeding is a decrease in milk production caused by a lack of stimulation of the hormones oxytocin and prolactin. The type of research used is Quasy Experiment with the design used post test only design with control group. The study was conducted in Aek Haruaya village, Portibi sub-district, North Padang Lawas district in 2022. The research population was mothers who had babies 0 – 2 months. Sampling technique with non-probability sampling with 10 respondents in the treatment group and 10 respondents in the control group. The results of the study concluded that the mean volume of milk expulsion in the treatment group was >20 ml, while the mean volume of milk expulsion in the control group was >40 ml. The results of the Independent T-Test test, p-value = 0.002, which means p<0.05, which means that there is an effect of oxytocin massage on increasing breast milk production.